2022
DOI: 10.21831/jorpres.v18i2.51646
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh latihan beban kombinasi dengan latihan aerobik terhadap berat badan dan persentase lemak tubuh pada remaja overweight

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh latihan beban metode sirkuit kombinasi dengan latihan aerobik terhadap berat badan dan persentase lemak tubuh pada remaja overweight. Desain penelitian dalam penelitian ini adalah pre-experimental design menggunakan one-group pretest-post test design. Sampel dipilih menggunakan teknik purposive sampling dengan kriteria remaja laki-laki overweight, sehingga diperoleh sampel sebanyak 20 orang. Teknik pengumpulan data menggunakan metode tes sebelum dan sesudah di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The study by Streb et al found that a combination of strength and aerobic exercise with linear periodization increased cardiorespiratory fitness with a mean difference of 4.2mL/kg/min, which was beneficial in reducing the risk of metabolic disease. Another study showed that combined weight training with aerobics can reduce body weight and body fat percentage in overweight people (Nurhadi et al, 2022). This is in line with the study of Jonathan Myers et al, which revealed that an increase in cardiorespiratory fitness by 4.8 mL/kg/min can reduce the risk of metabolic disease by 56% (Nylén et al, 2019).…”
Section: Resultssupporting
confidence: 66%
“…The study by Streb et al found that a combination of strength and aerobic exercise with linear periodization increased cardiorespiratory fitness with a mean difference of 4.2mL/kg/min, which was beneficial in reducing the risk of metabolic disease. Another study showed that combined weight training with aerobics can reduce body weight and body fat percentage in overweight people (Nurhadi et al, 2022). This is in line with the study of Jonathan Myers et al, which revealed that an increase in cardiorespiratory fitness by 4.8 mL/kg/min can reduce the risk of metabolic disease by 56% (Nylén et al, 2019).…”
Section: Resultssupporting
confidence: 66%